What Makes Us Human? The Interdisciplinary Challenge to Theological Anthropology and Christology - Van Huyssteen, J. Wentzel (Toronto journal of theology, 2010)
In this paper I argue for a theology that ought to be present in the interdisciplinary conversation that constitutes our public discourse, including the secular academy. I contend that the question of what makes us human can be answered only by pointing to the central theme of self and personhood. Already in early hominid evolution, the evolution of some of our most distinctive traits like consciousness, imagination, sexuality, moral awareness, language, and the religious disposition present us with a robust notion of embodied personhood. This strongly affirms the emergence of symbolic religious behaviour in our species. Ultimately I argue how a responsible account of the evolution of human distinctiveness, both theologically and scientifically, makes it possible to reach deep into theology and ask the ontological question about the personhood and identity of Jesus, as well as the ethical question why we should do what Jesus did.